An analysis of trade flows between BRICS and European Union: a quantitative assessment. Issue 4 (2nd October 2021) - Nori, Usha; Mishra, R. K.
Abstract: BRICS with their outward oriented strategy became the most influential group in international arena. Their economic and political weight which induces the negotiations/discussions with EU, lends the EU a special responsibility for the deeper integration of BRICS. Therefore, the economic impact of EU on the members of BRICS, post 2008 crisis and amidst Brexit declaration is essential to understand and how it affects the trade flows assumes a lot of significance. Against this backdrop, the study attempts to analyse the trade flows and its determinants between EU and BRICS applying gravity model. The estimated results reveal that economic size, market size, distance and the Brexit policy have significant effect on bilateral trade flows between BRICS and EU. BRICS future negotiations with EU as a unified single entity are desirable to expand beyond trade focussing on investments particularly for infrastructure building, technology upgradation and skill development. The study recommends product diversification and digitisation of economies for a smooth and fair trade and to mitigate the risks of present pandemic.